Dinamika Pengelolaan Sumber Daya Air - Nana Kristiawan (Muqoddima Jurnal Pemikiran dan Riset Sosiologi, 2020)
The aims of this research is to analyses the existence of the authority of local leaders on the water resources management, especially in Lake Kemuning, Cimanggis, Bogor, West Java. Basic principles design of pre-existing system (PES) which showing 6 variables: rules, rights, authority or leadership, sanction, and monitoring, accountability and enforcement, to be the main perspective in this cases. The result of this research showing that water management in Lake Kemuning trully influenced by local power leaders (persons or organization) although there are several legal regulation that govern. The role of local leaders is still remains a major, especially on the practical level. Some of the main roles of local leaders include: directing residents to maintain cleanliness, by providing rules in the form of prohibition of throwing garbage in the lake and fishing using nets and not throwing dirt and making noise through dangdut music around Kemuning Lake.